Determination of Heavy Metals in Fish Tissues, Water and Sediment from Epe and Badagry Lagoons, Lagos, Nigeria - R. A. Olowu; O. O. Ayejuyo; G. O. Adewuyi; I. A. Adejoro; A. A. B. Denloye; A. O. Babatunde; A. L. Ogundajo (E-Journal of Chemistry)
Water samples, sediments, tilapia and cat fishes from each of Epe and Badagry lagoons in Lagos State, Nigeria were analyzed quantitatively for the presence of zinc, nickel and iron using Perking Elmer atomic absorption spectrophotometer. The sediment contains higher concentration of Fe with a value of 13.30 µg/g against 8.400 µg/g in fishes and 7.30 mg/L in water. Studies on the different parts of the fish revealed higher concentrations of 4.00 µg/g Ni on the head of tilapia fish followed by 2.40 µg/g Ni in the intestine of cat fish. The highest concentration of 1.95 µg/g Zn was detected on the head of the cat fish while the lowest concentration with a value of 0.16 µg/g was recorded in tilapia head. The concentration of Zn in the water is within the limits permitted by the Lagos State Environmental Protection Agency (LASEPA) of 1.0 mg/L Zn set for water. None of the trace metals investigated was above the maximum permissible level set by world health organization ( WHO).